Little lemur laughing - Seigal, Joshua; Piascik, Chris (London : Bloomsbury Academic, 2017)
A dragon's sneeze, a dinosaur, a wizard's spell, a monster's claw. All these things and many more - that's what's in a poem. An exciting collection of poems from talented young poet Joshua Seigal, perfect for introducing children to poetry.
Primary
800-899
Keywords: Children's poetry, English; Children -- Poetry; Animals -- Poetry